2011
DOI: 10.1007/s11240-011-9916-8
|View full text |Cite
|
Sign up to set email alerts
|

A two-stage pretreatment of seedlings improves adventitious shoot regeneration in sugar beet (Beta vulgaris L.)

Abstract: The effects of a two-stage pretreatment of seedlings on the subsequent shoot regeneration capacity were investigated. Pretreated seedlings were obtained by germinating seeds on three different germination media and then further culturing on six different growth media. Lamina and petiole explants of two sugar beet (Beta vulgaris L.) breeding lines were then excised from the pretreated seedlings and cultured on five different shoot regeneration media. In both breeding lines, petiole explants produced significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
1
1
0
2
Order By: Relevance
“…Generally, we observed that explant cultured on hormone free medium produced lower percentage regeneration and this observation become clear when comparison of regeneration response in explants culture on hormone free media and those cultured on media containing BAP was made irrespective of These findings were also consistent with reports in cowpea (Raveendar et al, 2009;Mamman et al, 2013) and in other recalcitrant species (Gurel et al, 2011;Choudharyet al, 2009).In previous reports, successful regeneration of multiple shoots in cowpea was achieved only in explants with no defined apical dominance. In this work, however, multiples shoots were regenerated from apical meristem of embryonic axes demonstrating efficacy of BAP in suppressing apical dominance and induction of multiple shoots syndrome in cowpea.…”
Section: Resultssupporting
confidence: 91%
“…Generally, we observed that explant cultured on hormone free medium produced lower percentage regeneration and this observation become clear when comparison of regeneration response in explants culture on hormone free media and those cultured on media containing BAP was made irrespective of These findings were also consistent with reports in cowpea (Raveendar et al, 2009;Mamman et al, 2013) and in other recalcitrant species (Gurel et al, 2011;Choudharyet al, 2009).In previous reports, successful regeneration of multiple shoots in cowpea was achieved only in explants with no defined apical dominance. In this work, however, multiples shoots were regenerated from apical meristem of embryonic axes demonstrating efficacy of BAP in suppressing apical dominance and induction of multiple shoots syndrome in cowpea.…”
Section: Resultssupporting
confidence: 91%
“…Buna ek olarak, oksin ilavesinin faydalı olmadığı, %3 sukroz içeren bir MS ortamı kullanılarak 1.0 mg/L NAA uygulanmasıyla sürgünlerde köklenmenin de sağlanabildiği belirlenmiştir [18]. Türkiye'de şeker pancarı ıslahında; bitki doku kültürü çalışmalarıyla genetik materyalin klonla [19][20][21][22][23][24][25][26][27], hücre kültürüyle [28], kallus kültürüyle [15], ovül kültürüyle [21,29] ve protoplast kültürüyle [30], çoğaltılmasına yönelik bir takım çalışmalar yürütülmüştür. Bitki doku kültürü çalışmalarıyla; aynı genetik yapıya sahip birçok birey; hızlı ve sağlıklı olarak çoğaltılabilmektedir [15,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionunclassified
“…Türkiye'de şeker pancarı ıslahında; bitki doku kültürü çalışmalarıyla genetik materyalin klonla [19][20][21][22][23][24][25][26][27], hücre kültürüyle [28], kallus kültürüyle [15], ovül kültürüyle [21,29] ve protoplast kültürüyle [30], çoğaltılmasına yönelik bir takım çalışmalar yürütülmüştür. Bitki doku kültürü çalışmalarıyla; aynı genetik yapıya sahip birçok birey; hızlı ve sağlıklı olarak çoğaltılabilmektedir [15,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Ancak, ıslah programına dâhil edilen önemli kültür bitkilerine yakın akraba doğal türlerinin bitki doku kültürü teknikleriyle çoğaltılmasına yönelik en uygun koşulların belirlenmesi ve tespiti için yeni çalışmalara ihtiyaç duyulmaktadır.…”
Section: Introductionunclassified
“…Many published studies report on the effects of various hormonal treatments on the regeneration, proliferation and propagation of different genotypes of sugar beet via diverse tissues (Mezei et al 2006, Mishutkina and Gaponenko 2006, Gürel et al 2011, Tomaszewska-Sowa 2012, Klimek-Chodacka and Baranski 2013, Tomita et al 2013. However, in spite of the evidence for hyperhydricity provided by them (e.g.…”
Section: Introductionmentioning
confidence: 99%